Development and validation of a questionnaire for assessing pathomorphoisis and pathoplasty of stereotypes in autism spectrum disorders and schizophrenia in childhood - L. Zh. Attaeva; I. V. Makarov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Relevance: repetitive behaviors, limited interests, and other unusual sensory behaviors often significantly affect the lives of many people with developmental disabilities, including but not limited to autism spectrum disorder (ASD) and childhood schizophrenia (PSD). Identification of specific patterns of atypical behavior in these disorders can improve the specificity of diagnoses and monitor response to treatment. Therefore, it would be useful to have an approved questionnaire for the assessment of pathomorphosis and pathoplasty of stereotypes in ASD and schizophrenia in childhood, aimed at parents and caregivers of children in this cohort. Objective: To develop and validate a questionnaire for assessing the manifestations and dynamics of stereotypes in ASD and ADHD in childhood, aimed at parents and guardians of children in this cohort, for further use in clinical practice. Materials and Methods: in accordance with international and Russian standards, a questionnaire was developed to assess the manifestations and dynamics of stereotypes and tested on a focus group of parents (legal representatives) of children diagnosed with ASD and PSD, followed by an assessment of the results of psychodiagnostic testing - reliability, validity and sensitivity of the results obtained. developed questionnaire. Statistical analysis was performed using Statistica, version 9.0. Results: according to the results of testing with the participation of a group of parents (legal representatives) of the selected cohort, the acceptability of the questionnaire and high validity rates were confirmed. The conducted factor analysis testifies to the adequacy of the grouping of questions of the questionnaire according to the expected factors and stable construct validity. Conclusion: the results obtained indicate the reliability, validity and sensitivity of the questionnaire for assessing the manifestations and dynamics of stereotypes in ASD and SDV in childhood and the possibility of its use in epidemiological studies both for clinical practice and for scientific purposes in the field of psychiatry.